Two flowering locus T (FT) homologs in Chenopodium rubrum differ in expression patterns - Cháb, David; Kolár, Jan; Olson, Matthew S; Storchová, Helena (Planta, 2008)
FLOWERING LOCUS T (FT) like genes are crucial regulators (both positive and negative) of flowering in angiosperms. We identified two FT homologs in Chenopodium rubrum, a short-day species used as a model plant for the studies of photoperiodic flower induction. We found that CrFTL1 gene was highly inducible by a 12-h dark period, which in turn induced flowering. On the other hand, photoperiodic treatments that did not induce flowering (short dark periods, or a permissive darkness interrupted by a night break) caused only a slight increase in CrFTL1 mRNA level. We demonstrated diurnal oscillation of CrFTL1 expression with peaks in the middle of a light period. The oscillation persisted under constant darkness. Unlike FT homologs in rice and Pharbitis, the CrFTL1 expression under constant darkness was very low. The CrFTL2 gene showed constitutive expression. We suggest that the CrFTL1 gene may play a role as a floral regulator, but the function of CrFTL2 remains unknown.
Keywords: Circadian Rhythm; Molecular Sequence Data; messenger RNA; sekvence aminokyselin; Photoperiod; Gene Expression Regulation, Plant; DNA, Complementary; Sequence Alignment; fotoperioda; cirkadiánní rytmus; Darkness; rostlinné proteiny; komplementární DNA; RNA, Messenger; Amino Acid Sequence; Plant Proteins; regulace genové exprese u rostlin; molekulární sekvence - údaje; Chenopodium; sekvenční seřazení; Flowers; květy; tma